Link between Urban Forests and Poverty: A Case of Study in a City of Argentina - Celemin, Juan Pablo (2022)
Urban forestry is considered a positive indicator of a city´s environment as it supplies many positive services to local communities. However not all the residents can benefit from it, especially in areas where trees are not native vegetation, such is the case of Mar del Plata (Argentina). In this research an integrated approach combining census data and satellite images shows that the residents of a forested residential area in Mar del Plata with good socioeconomic conditions benefit with a higher Normalized Difference Vegetation Index (NDVI) and lower temperature than most parts of the city.